Clinical activity and safety of Pembrolizumab in Ipilimumab pre-treated patients with uveal melanoma. (3rd May 2016) - Karydis, Ioannis; Chan, Pui Ying; Wheater, Matthew; Arriola, Edurne; Szlosarek, Peter W.; Ottensmeier, Christian H.
ABSTRACT: Background : Untreated metastatic uveal melanoma (UM) carries a grave prognosis. Unlike cutaneous melanoma (CM), there are no established treatments known to significantly improve outcomes for a meaningful proportion of patients. Inhibition of the PD1–PDL1 axis has shown promise in the management of CM and we here report a two center experience of UM patients receiving pembrolizumab.Methods : To assess the efficacy and safety of pembrolizumab, we retrospectively analyzed outcome data of 25 consecutive UM patients participating in the MK3475 expanded access program (EAP) who received pembrolizumab at 2 mg/kg 3 weekly. Tumor assessment was evaluated using RECIST 1.1 and immune-related Response Criteria (irRC) by CT scanning. Toxicity was recorded utilizing Common Terminology Criteria for Adverse Events ("CTCAE") v4.03.Results : Twenty-five patients were identified receiving a median of six cycles of treatment. Two patients achieved a partial response and six patients stable disease. After a median follow-up of 225 d median progression free survival (PFS) was 91 d and overall survival (OS) was not reached. There was a significant trend for improved outcomes in patients with extrahepatic disease progression as opposed to liver only progression at the outset. Five patients experienced grade 3 or 4 adverse events (AEs); there were no treatment related deaths.Conclusions : Pembrolizumab 2mg/kg q3w is a safe option in UM patients. Disease control rates, particularly in the subgroup of patients without progressive liver disease at the outset are promising; these results merit further investigation in clinical trials possibly incorporating liver targeted treatment modalities.